DECOHERENCE-FREE SUBSPACES FOR OPEN QUANTUM RANDOM WALKS ON GRAPHS (2016)
We study decoherence-free subspaces in a type of Quantum Markov Semigroups called continuous-time open quantum random walks on graphs. We measure the temporary changes of quantum correlations using geometric quantum discord with bures distance under some assumptions about the semigroup. In particular, we characterize the decay of correlations to zero, showing that turns out to be closely related with the structure of decoherence-free subspace.